Effectiveness of a Dynamic Ergonomic Chair in Individuals with Postural Dysfunction (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Low back pain in postnatal women is a major issue. So, lumbar curvature is a key feature tomaintain core strength for which it has to be assessed. The individual variations in spinal curvature andlordotic pattern signifies the bio mechanics of the spine and it responds according to the load / activities.To find out the pre-test measures of flexibility, functional capacity and discomfort level related to lumbarspine in the subjects with postural dysfunctions. To find out the post-test flexibility, functional capacity anddiscomfort level in the subjects with postural dysfunctions. To analyze the difference between the pre-testand post-test values. People should also have awareness about the posture maintenance. So, early assessmentis necessary. Also secondary factors like the type of shoes wear, Occupation and Lifestyle can influence thespinal curvatures which can be dealt with easier with the outcome of the research.Methodology: In this experimental study, 29 people with age group of 25 to 60 years who have chronic lowback pain. Their lumbar spine flexibility, functional capacity, and discomfort level was measured pre-testand post-test. Results were obtained and compared.Result: The average mean value of lumbar spine flexibility pre-test measured with schober test was 1.81while post-test was 2.08. Average mean value of VAS for lumbar spine was 6.06 while post-test was 3.24.Average mean value for pre-test functional capacity measured with 6 min walk test was647.58 while posttest was 665.17.Conclusion: On comparing summary score of lumbar spine flexibility, VAS, and functional capacity, thedifferences showed were 0.27 cms, 2.82, 17.59 metres respectively.So, we can conclude that there was a signicant difference in the improvement of lumbar spine flexibility,functional capacity and also decrease in pain after the treatment.